Perceptions of partial gland ablation for prostate cancer among men on active surveillance: a qualitative study. Issue 1 (21st April 2021) - Hur, Sonia; Tzeng, Michael; Cricco-Lizza, Eliza; Basourakos, Spyridon; Yu, Miko; Ancker, Jessica; Abramson, Erika; Saigal, Christopher; Ross, Ashley; Hu, Jim
Abstract : Objectives: Partial gland ablation (PGA) therapy is an emerging treatment modality that targets specific areas of biopsy-proven prostate cancer (PCa) to minimize treatment-related morbidity by sparing benign prostate. This qualitative study aims to explore and characterize perceptions and attitudes toward PGA in men with very-low-risk, low-risk, and favorable intermediate-risk PCa on active surveillance (AS). Design: 92 men diagnosed with very-low-risk, low-risk, and favorable intermediate-risk PCa on AS were invited to participate in semistructured telephone interviews on PGA. Setting: Single tertiary care center located in New York City. Participants: 20 men with very-low-risk, low-risk, and favorable intermediate-risk PCa on AS participated in the interviews. Main outcome measures: Emerging themes on perceptions and attitudes toward PGA were developed from transcripts inductively coded and analyzed under standardized methodology. Results: Four themes were derived from 20 interviews that represent the primary considerations in treatment decision-making: (1) the feeling of psychological safety associated with low-risk disease; (2) preference for minimally invasive treatments; (3) the central role of the physician; (4) and the pursuit of treatment options that align with disease severity. Eleven men (55%) expressed interest in pursuing PGA only if their cancer were to progress, while nine men (45%) expressed interest at the current moment. Conclusions: Although an emerging treatment modality, patients were broadly accepting of PGA for PCa, with men primarily debating the risks versus benefits of proactively treating low-risk disease. Additional research on men's preferences and attitudes toward PGA will further guide counseling and shared decision-making for PGA.